The effectiveness and safety of subcutaneous immunotherapy for inhalable allergens in patients with respiratory allergies - Francisco Valle-Rodríguez; Aida Inés López- García; Daniela Rivero-Yeverino; Chystopherson Gengyny Caballero-López; José Sergio Papaqui-Tapia; Israel Pablo Ruiz-Márquez; Juan Jesús Ríos-López; Johav Yael Sánchez-Villalobos (Revista Alergia México, 2019)
Background: Specific immunotherapy is a treatment aimed at modifying the course of the allergic disease, with which important immunological and clinical changes are achieved.